2007
DOI: 10.1111/j.1750-3841.2007.00346.x
|View full text |Cite
|
Sign up to set email alerts
|

Application of Atomic Force Microscopy as a Nanotechnology Tool in Food Science

Abstract: Atomic force microscopy (AFM) provides a method for detecting nanoscale structural information. First, this review explains the fundamentals of AFM, including principle, manipulation, and analysis. Applications of AFM are then reported in food science and technology research, including qualitative macromolecule and polymer imaging, complicated or quantitative structure analysis, molecular interaction, molecular manipulation, surface topography, and nanofood characterization. The results suggested that AFM coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
82
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(82 citation statements)
references
References 69 publications
0
82
0
Order By: Relevance
“…Epron et al (2004), when studying CO 2 emissions from soil cultivated with eucalyptus, concluded that the bivariate model, including soil temperature and moisture, did not explain the temporal variations in CO 2 emission; the univariate model, with the use of soil moisture, was more efficient. Besides soil moisture and temperature, FCO 2 in SG-5 presented an indirect relationship with air-filled pore space of R 2 = 0.73 to SG-5 and R 2 = 0.51 to SG-10 ( Figure 4e) and this may be related to the stimulation of microbial activity, which was promoted by higher soil moisture and had a great influence on FCO 2 (Davidson and Swank, 1986), especially in the rainy period, when AFPS was lower than in the dry period.…”
Section: Temporal Variabilitymentioning
confidence: 99%
“…Epron et al (2004), when studying CO 2 emissions from soil cultivated with eucalyptus, concluded that the bivariate model, including soil temperature and moisture, did not explain the temporal variations in CO 2 emission; the univariate model, with the use of soil moisture, was more efficient. Besides soil moisture and temperature, FCO 2 in SG-5 presented an indirect relationship with air-filled pore space of R 2 = 0.73 to SG-5 and R 2 = 0.51 to SG-10 ( Figure 4e) and this may be related to the stimulation of microbial activity, which was promoted by higher soil moisture and had a great influence on FCO 2 (Davidson and Swank, 1986), especially in the rainy period, when AFPS was lower than in the dry period.…”
Section: Temporal Variabilitymentioning
confidence: 99%
“…The measurement of average particle size is based on a number average, and also the size distribution depends on the number of measured particles. Therefore, it is important to analyze enough particles to obtain statistically significant results [7,26,61,127,128,132,144]. Satpati et al worked on synthesis and investigation of nano-crystalline materials of the tobacco sample and its ash using high-resolution TEM and related techniques.…”
Section: Microscopy Techniquesmentioning
confidence: 99%
“…In addition to more conventional ones, i.e., LMs e bright field and polarized LM, fluorescence microscopy, CLSM (Dufour, 2011;El-Bakry & Sheehan, 2014;Sheen, Bao, & Cooke, 2008;van de Velde, van Riel, & Tromp, 2002), EFLM (Peighambardoust, Dadpour, & Dokouhaki, 2010) e and EMs e SEM and TEM (El-Bakry & Sheehan, 2014), cryo-SEM and cryo-TEM, STEM, ESEM and ASEM, EDX spectroscopy and microanalysis (Gatti, Tossini, Gambarelli, Montanari, & Capitani, 2009;B. James, 2009), also SPM techniques -AFM, SNOM, STM (Liu & Cheng, 2011;H. Yang et al, 2007) e have been put forward and are being increasingly applied for nanocharacterization of food.…”
Section: Scanning Probe Microscopy Based Techniques For Nanoscale Chamentioning
confidence: 99%
“…Due to its relatively wide diffusion and straightforward sample preparation, AFM is the most widely used SPM technique in food-related studies (Liu & Cheng, 2011;H. Yang et al, 2007).…”
Section: Scanning Probe Microscopy Based Techniques For Nanoscale Chamentioning
confidence: 99%